Economic and Social Costs of Noma: Design and Application of an Estimation Model to Niger and Burkina Faso - Mpinga, Emmanuel Kabengele; Srour, Margaret Leila; Moussa, Marie-Solène Adamou; Dupuis, Marc; Kagoné, Moubassira; Grema, Maïna Sani Malam; Zacharie, Ngoyi-Bukonda; Baratti-Mayer, Denise (Tropical Medicine and Infectious Disease, 2022)
Background: While noma affects hundreds of thousands of children every year, taking their lives, disfiguring them and leaving them permanently disabled, the economic and social costs of the disease have not been previously estimated. An understanding of the nature and levels of these costs is much needed to formulate and implement strategies for the prevention and control of this disease, or to mitigate its burden. The objectives of our study were to develop a model for estimating the economic and social costs of noma and to provide estimates by applying this model to the specific contexts of two countries in the “noma belt”, namely Burkina Faso and Niger. Methods: Three main approaches were used. The estimation of prevalence levels of potential noma cases and of cases that should receive and actually do receive medical care was carried out using a literature review. The documentary approach made it possible to estimate the direct costs of noma by analyzing the database of a non-governmental organization operating in this field and present in both countries. Indirect costs were estimated using the human capital method and the cost component analysis technique. Results: The direct costs of care and management of noma survivors amount to approximately USD 30 million per year in Burkina Faso, compared to approximately USD 31 million in Niger. They mainly include costs for medical treatment, surgery, hospital stays, physiological care, psychological care, social assistance, schooling, vocational training and care abroad. Indirect costs are estimated at around 20 million in lost production costs in Burkina and around 16 million in Niger. Costs related to premature deaths are estimated at more than USD 3.5 billion in Burkina Faso and USD 3 billion in Niger. Finally, the costs to survivors who are unable to marry are around USD 13.4 million in Burkina and around USD 15 million in Niger. Intangible costs were not calculated. Conclusions: The neglect of noma and inaction in terms of prevention and control of the disease have enormous economic and social costs for households, communities and states. Future studies of this kind are necessary and useful to raise awareness and eradicate this disease, which impacts the health and well-being of children and results in lifelong suffering and severe economic and social costs to survivors and their families.